Workforce Projections 2010–2020: Annual Supply and Demand Forecasting Models for Physical Therapists Across the United States. Issue 1 (1st January 2016) - Landry, Michel D.; Hack, Laurita M.; Coulson, Elizabeth; Freburger, Janet; Johnson, Michael P.; Katz, Richard; Kerwin, Joanne; Smith, Megan H.; Wessman, Henry C. "Bud"; Venskus, Diana G.; Sinnott, Patricia L.; Goldstein, Marc
Abstract : Background: Health human resources continue to emerge as a critical health policy issue across the United States. Objective: The purpose of this study was to develop a strategy for modeling future workforce projections to serve as a basis for analyzing annual supply of and demand for physical therapists across the United States into 2020. Design: A traditional stock-and-flow methodology or model was developed and populated with publicly available data to produce estimates of supply and demand for physical therapists by 2020. Methods: Supply was determined by adding the estimated number of physical therapists and the approximation of new graduates to the number of physical therapists who immigrated, minus US graduates who never passed the licensure examination, and an estimated attrition rate in any given year. Demand was determined by using projected US population with health care insurance multiplied by a demand ratio in any given year. The difference between projected supply and demand represented a shortage or surplus of physical therapists. Results: Three separate projection models were developed based on best available data in the years 2011, 2012, and 2013, respectively. Based on these projections, demand for physical therapists in the United States outstrips supply under most assumptions. Limitations: Workforce projection methodology research is based on assumptions using imperfect data; therefore, the results must be interpreted in terms of overall trends rather than as precise actuarial data–generated absolute numbers from specified forecasting. Conclusions: Outcomes of this projection study provide a foundation for discussion and debate regarding the most effective and efficient ways to influence supply-side variables so as to position physical therapists to meet current and future population demand. Attrition rates or permanent exits out of the profession can have important supply-side effects and appear to have an effect on predicting future shortage or surplus of physical therapists.